2015
DOI: 10.1177/0146167215580776
|View full text |Cite
|
Sign up to set email alerts
|

Using High-Level Construal and Perceptions of Changeability to Promote Self-Change Over Self-Protection Motives in Response to Negative Feedback

Abstract: Diagnostic negative information presents people with a motivational dilemma. Although negative feedback can provide useful information with which to guide future self-improvement efforts, it also presents short-term affective costs. We propose that construal level, jointly with the perceived changeability of the feedback domain, determines whether people choose to accept or dismiss such information. Whereas low-level construal promotes short-term self-protection motivation (promoting dismissal), high-level con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…The results suggest the importance of progress monitoring and goal specificity in determining behavioral reactions to feedback. The results of the present studies are consistent with other work that has shown the importance of the goal specificity and feedback (Aarts and Dijksterhuis 2000;Belding et al 2015;Fishbach and Dhar 2005;Fishbach et al 2006;Förster et al 2005;Gollwitzer and Moskowitz 1996;Hsee and Abelson 1991;Karsh and Eyal 2015;Kluger and DeNisi 1996;Locke and Latham 2002). The present experiments focused on unexplored aspects of goals striving and discovered that progress monitoring and goal specificity are indeed important factors that determine how feedback valence affects goal striving.…”
Section: Discussionsupporting
confidence: 92%
“…The results suggest the importance of progress monitoring and goal specificity in determining behavioral reactions to feedback. The results of the present studies are consistent with other work that has shown the importance of the goal specificity and feedback (Aarts and Dijksterhuis 2000;Belding et al 2015;Fishbach and Dhar 2005;Fishbach et al 2006;Förster et al 2005;Gollwitzer and Moskowitz 1996;Hsee and Abelson 1991;Karsh and Eyal 2015;Kluger and DeNisi 1996;Locke and Latham 2002). The present experiments focused on unexplored aspects of goals striving and discovered that progress monitoring and goal specificity are indeed important factors that determine how feedback valence affects goal striving.…”
Section: Discussionsupporting
confidence: 92%
“…Although there are broader sources for feedback, classic challenges remain. People often find criticism unpleasant, react negatively to it, and perceive the feedback and source as unfair [5,21]. Negative reactions to feedback can lead to reduced effort during revisions [10,17], decreased motivation and commitment to task goals [17], and hindered cognitive abilities [33,39].…”
Section: Introductionmentioning
confidence: 99%
“…Under an abstract style, individuals prioritize future benefits over immediate costs, something that is directly related to self-control, a self-regulation strategy that specifically implies acting to achieve distal goals (Fujita, 2008(Fujita, , 2011Fujita & Carnevale, 2012). Based on CLT, Fujita and collaborators proposed that an abstract construal facilitates greater self-control by focusing people's attention on the final goals and thus favors healthier and beneficial longterm choices (Belding et al, 2015;Ledgerwood et al, 2010;Libby et al, 2007;Fujita, 2008;Fujita & Han, 2009). A recent study in Nicaragua found that adolescents under severe scarcity who presented a concrete style of thinking reported the highest rates of past and future risk behaviors (Aguilar et al, 2020).…”
mentioning
confidence: 99%